Ownership structure, risk taking and firm performance: a case for an integrative framework - Almuqren, Mohammed Khalid S.; Ab Razak, Nazrul Hisyam; Mahat, Fauziah; Md Nassir, Annuar (International Journal of Economics, Commerce and Management publishing, 2017)
Studies on ownership structure and firm performance are inexhaustible. This is due to the growing contradictory, inconclusive and inconsistent empirical findings which give rise to growing concerns and suggestions for the integration of latent variables to best explain the observed unclear relationship. This would mean adopting more of an integrated (moderation or mediation) rather than direct research framework in an attempt to explain the relationship between ownership structure and firm's performance better. This paper thus examined the ownership structure and firm performance with risk-taking behaviour as a moderator. As conceptual paper, a review of agency and stewardship theories as well as prospect theory along with each dimension of ownership structure is conducted. From the extensive review, it was found that risk taking is an integral part of organizational life. Consequently, an integrative framework that incorporates risk-taking as a moderator in the relationship between ownership structure and firm performance is proposed. This paper concluded that the application of this framework would offer better explanation of the relationship between ownership structure and firm performance taking into account the risk preferences of the enterprise.